2010
DOI: 10.4269/ajtmh.2010.09-0689
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus Infection among Animals and Humans in Xinjiang, China: Possibility of Swine to Human Transmission of Sporadic Hepatitis E in an Endemic Area

Abstract: Abstract. Hepatitis E is a worldwide public health problem, especially in areas with poor sanitation. This study examines the potential hepatitis E virus (HEV) animal reservoirs and the current status of HEV infection among animals and humans in an endemic area of Xinjiang, China. One thousand five hundred twenty-one serum samples from 12 different animal species and 296 sera from humans were detected for anti-HEV with an in-house enzyme immunoassay, and partial HEV RNA was amplified with a reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…Several studies had been reported from Japan of autochthonous HEV infections acquired from the consumption of undercooked pig liver or intestine [49,50], wild hog [68] or deer [51,69]. Antibodies to HEV were detected in several animal species in western China but HEV RNA has only been detected in pigs and human cases [70]. Genotype 4 HEV strains have been isolated from swine and a human hepatitis case in western China with 99% identity over the entire genome [70].…”
Section: Hev Infections In Industrialized Countries In Asiamentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies had been reported from Japan of autochthonous HEV infections acquired from the consumption of undercooked pig liver or intestine [49,50], wild hog [68] or deer [51,69]. Antibodies to HEV were detected in several animal species in western China but HEV RNA has only been detected in pigs and human cases [70]. Genotype 4 HEV strains have been isolated from swine and a human hepatitis case in western China with 99% identity over the entire genome [70].…”
Section: Hev Infections In Industrialized Countries In Asiamentioning
confidence: 97%
“…Antibodies to HEV were detected in several animal species in western China but HEV RNA has only been detected in pigs and human cases [70]. Genotype 4 HEV strains have been isolated from swine and a human hepatitis case in western China with 99% identity over the entire genome [70]. Both genotype 3 and 4 HEV strains have been isolated from human cases of HE in Japan [59][60][61]71,72].…”
Section: Hev Infections In Industrialized Countries In Asiamentioning
confidence: 97%
“…First, it incorporates antigens representing all four HEV genotypes, so allowing for the detection of antibodies generated in the host regardless of the genotype of the infecting HEV. Other DASAs developed for anti-HEV detection (14,22,55,63) mostly utilize antigenic preparations derived from one genotype only. Second, the highly immunodominant p166 antigens (37) are used to capture antibody, as well as to report its solid-phase capture, thereby conferring both sensitivity and specificity to anti-HEV detection.…”
Section: Discussionmentioning
confidence: 99%
“…Except for farmed Rex rabbits (Oryctolagus cuniculus) in China (15,16,36), the evidence for HEV as being enzootic in species other than pigs, boars, deer, and chickens is weak, for several reasons. First, HEV RNA or antigen is infrequently, if ever, detected in their blood, bile or feces (1,14,16,25,35,51,63,69). Although HEV RNA sequences have occasionally been amplified from single animals (71,72), such detection would not necessarily implicate HEV enzooticity in the species to which those animals belong; rather, they could be accidental hosts or their samples (especially if of fecal origin) might have been contaminated with HEV shed from true maintenance hosts sharing the same habitats (58).…”
mentioning
confidence: 99%
See 1 more Smart Citation